Documentario 2. - Arienti, Stefano; Cingolani, Marco; Colapietro, Marco; Fend, Peter; Fontana, Massimiliano; Friedmann, Alan; Gentili, Filippo; Graziolo, Elio; Kaufmann, Massimo; Moura, Leonel; Obrist, Hans Ulrich; Pietrantonio, Giacinto Di; et al. (Milano : Documentario, 1993)
Graham, Dan ; Biefer & Zgraggen ; Boltanski, Christian ; Muntadas, Antoni ; Adams, Dennis ; Dunning, Jeanne ; Gonzalez-Torres, Felix ; Krystufek, Elke ; Vilmouth, Jean-Luc ; Leonard, Zoe ; Haacke, Hans ; Gillick, Liam ; Accardi, Carla ; Ad Hoc ; Alviani, Getulio ; Armleder, John ; Bijl, Guillaume ; Boetti, Alighiero ; Bond, Henry ; Bulloch, Angela ; Casciani, Stefano ; Cucchi, Enzo ; Delvoye, Wim ; Garutti, Alberto ; Gillick, Liam ; IRWIN ; Kozaris, Dimitris ; Nannucci, Maurizio ; Odenbach, Marcel ; Ontani, Luigi ; Paladino, Mimmo ; Pisani, Vettor ; Pistoletto, Michelangelo ; Prigov, Dimitrij ; Prini, Emilio ; Rudiger, Bernhard ; Schütte, Thomas ; Shimamoto, Shozo ; Spalletti, Ettore ; Steinbach, Haim ; Trockel, Rosemarie ; Ben ; Cattelan, Maurizio ; Cingolani, Marco ; Dokoupil, Jiri Georg ; Fantin, Emilio ; Martegani, Amedeo ; Pancrazzi, Luca ; Ruff, Thomas ; Samore, Sam ; Scholte, Rob ; Sossella, Ivano & Formento, Marco ; Verkerk, Emo ; Airo, Mario ; Anüll, Ian ; Bacher, Lutz ; Calle, Sophie ; Döorsen, Fieroza ; Fairhurst, Angus ; Faust, Gretchen ; Gonzalez-Foerster, Dominique ; Jacob, Wendy ; Kelley, Mike ; Kilimnik, Karen ; King, Ashley ; Krystufek, Elke ; Lane, Abigail ; Lemieux, Annette ; Majoli, Monica ; Marisaldi, Eva ; McCarthy, Paul ; Noland, Cady ; Pivi, Leonardo ; Williams, Sue ; Zittel, Andrea
Italiaans - Engels
Documentario2, Spazio Opos, Milano, 15.01. - 30.01.1993
boek